ANALYSIS OF PAYROLL ACCOUNTING INFORMATION SYSTEM IN EFFECTIVENESS OF INTERNAL CONTROL AT PT PERKEBUNAN NUSANTARA IV MEDAN - Adella, Cindy (Proceeding International Seminar of Islamic Studies, 2024)
The payroll accounting information system is a system designed to facilitate accurate and precise employee salary calculation transactions. The purpose of this study is to determine the payroll accounting information system that has been implemented by PT. Perkebunan Nusantara IV Medan and to find out whether the applied payroll accounting information system has good internal control. This research method uses a descriptive research approach and qualitative data types and quantitative data types. Data collection techniques in this study used interviews and documentation techniques. The data analysis technique used in this research is descriptive analysis. The result of this study is the payroll accounting information system at PT. Perkebunan Nusantara IV Medan has been running effectively. From the results of the study it can be explained that the employee payroll system at PT Perkebunan Nusantara IV Medan is carried out by bank transfers to each employee's account which is calculated using the payroll application based on basic salary, allowances and deductions. Internal Control at PT. Perkebunan Nusantara IV Medan has been running quite effectively, because every payroll transaction that has been made has been verified and re-checked for accuracy before payment of salaries is made.